11g, a Potent Antifungal Candidate, Enhances Candida albicans Immunogenicity by Unmasking β-Glucan in Fungal Cell Wall - Huang, Xin; Liu, Yu; Ni, Tingjunhong; Li, Liping; Yan, Lan; An, Maomao; Zhang, Dazhi; Jiang, Yuanying (Frontiers in Microbiology, 2020)
In the course of optimizing GPI biosynthesis inhibitors, we designed and synthetized a 2-aminonicotinamide derivative named 11g. After evaluating the antifungal activity of compound 11g in vitro, we investigated the influences of 11g on fungi immunogenicity. In addition, we also took advantages of murine systemic candidiasis model to investigate the protective effects of 11g in vivo. Results show that 11g exhibited potent antifungal activity both in vitro and in vivo. Further study shows that 11g caused the unmasking of fungi β-glucan layer, leading to stronger immune responses in macrophages through Dectin-1. These results suggest that 11g is a very promising antifungal candidate, which assists in eliciting stronger immune responses to help host immune system disposing pathogens. The discovery of 11g might expand the tool box of fungal infection treatment.